Pengaruh pendidikan kesehatan terhadap tingkat pengetahuan ibu tentang flu singapura pada anak balita - Arifin, Rani Fitriani; Sulasih, Sri (Jurnal Ilmiah STIKES Yarsi Mataram, 2021)
The aim of this study to determine the influence of health education on mother’s knowledge level about flu Singapore in children under five years old. This study design was Experimental Quasi with One Group Pre Test and Post Test Design. The sample in this study were 15 respondents with a quota sampling techniques. The study starts from initial data retrieval on February 20, 2017 and the implementation of the research was conducted on 15 June 2017 until 13 July 2017. The analysis used in this study is univariate analysis and bivariate analysis. The study results was Wilcoxon test, there are differences in pretest and posttest mother’s knowledge level about flu Singapore in children under five years old indicated that the p value of 0,006 (<0,05). The conclusion of this study there was of health education on mother’s knowledge level about flu Singapore in children under five years old.